2008
DOI: 10.1002/art.24177
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of nicotinic acetylcholine receptors attenuates collagen‐induced arthritis in mice

Abstract: Objective. The parasympathetic nervous system, through the vagus nerve, can down-regulate inflammation in vivo by decreasing the release of cytokines, including tumor necrosis factor ␣ (TNF␣), by activated macrophages. The vagus nerve may exert antiinflammatory actions via a specific effect of its principal neurotransmitter, acetylcholine, on the ␣7 subunit of nicotinic acetylcholine receptors (␣7nAChR) on macrophages. The present study was undertaken to obtain insight into the role of the cholinergic antiinfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
208
1
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 239 publications
(233 citation statements)
references
References 29 publications
18
208
1
6
Order By: Relevance
“…Still, it has been shown that electrical and pharmacologic stimulation of the vagus nerve results in decreased carrageenan-induced paw inflammation in rats (23). Consistent with these results, we recently demonstrated that manipulation of the vagus nerve has an effect on arthritis activity in the collageninduced arthritis (CIA) model of RA (24). In addition, treatment with ␣7nAChR-specific agonists reduced joint inflammation in this model.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Still, it has been shown that electrical and pharmacologic stimulation of the vagus nerve results in decreased carrageenan-induced paw inflammation in rats (23). Consistent with these results, we recently demonstrated that manipulation of the vagus nerve has an effect on arthritis activity in the collageninduced arthritis (CIA) model of RA (24). In addition, treatment with ␣7nAChR-specific agonists reduced joint inflammation in this model.…”
supporting
confidence: 82%
“…Recently we have shown that in murine CIA, nicotine treatment as well as treatment with AR-R17779 resulted in a significant decrease in clinical signs of arthritis, joint destruction, and TNF␣ expression in the synovium and plasma (24). In the present study we show the significant decrease of IL-6 and IL-8 production by FLS after treatment with nicotine or AR-R17779; these are important proinflammatory cytokines involved in the pathogenesis of RA (37,43,44).…”
supporting
confidence: 69%
“…Humoral mechanisms that restrain or inhibit these damaging responses include glucocorticoid hormones, soluble cytokine receptors, IL-10, transforming growth factor (TGF)-β and other antiinflammatory cytokines. Activation of cholinergic receptors is also known to regulate immune system activity (2)(3)(4)(5)(6)(7)(8)(9). Recent insights in protective mechanisms have revealed that neural circuits suppress release of damaging cytokines and that neural regulation of immune cell activation is an ancient mechanism dating back to nematode worms, a primitive animal with rudimentary nervous and immune systems (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…We reported that activation of α7nAChR by nicotine and a specific α7nAChR agonist significantly attenuated indomethacin-induced small intestinal lesions (28). Similar beneficial action mediated by the activation of α7nAChR has been demonstrated in lethal sepsis (24), caeruleininduced pancreatitis (25), postoperative ileus (26), and collagen-induced arthritis (27), as well as colonic inflammation (22,23). Based on these studies and our own, we conclude that α7nAChR may be a promising target for preventing inflammatory disorders, including NSAIDinduced small intestinal ulceration.…”
Section: Discussionmentioning
confidence: 58%